Jean Harris Local Environmental Collection DedicationJean Harris Local Environmental Collection Dedication (CSU Channel Islands Library)
With speakers Dr. Richard Rush - President, CSU Channel Islands. Amy Wallace - Dean of the Library. Dr. Sean Anderson - Assistant Professor, ESRM Program. Carmen Ramirez - Oxnard City Council. Dr. Tom Holden - Mayor of Oxnard. Sponsored by the John Spoor Broome Library and the Environmental Science & Resource Management Program.With speakers Dr. Richard Rush - President, CSU Channel Islands. Amy Wallace - Dean of the Library. Dr. Sean Anderson - Assistant Professor, ESRM Program. Carmen Ramirez - Oxnard City Council. Dr. Tom Holden - Mayor of Oxnard. Sponsored by the John Spoor Broome Library and the Environmental Science & Resource Management Program.